2009
DOI: 10.1007/s10930-009-9217-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effects of α-Crystallin and GroEL on the Kinetics of Thermal Aggregation of Rabbit Muscle Glyceraldehyde-3-Phosphate Dehydrogenase

Abstract: Effects of alpha-crystallin and GroEL on the kinetics of thermal aggregation of rabbit muscle glyceraldehyde-3-phosphate dehydrogenase (GAPDH) have been studied using dynamic light scattering and analytical ultracentrifugation. The analysis of the initial parts of the dependences of the hydrodynamic radius of protein aggregates on time shows that in the presence of alpha-crystallin or GroEL the kinetic regime of GAPDH aggregation is changed from the regime of diffusion-limited cluster-cluster aggregation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…This fact indicates that GAPDH aggregation proceeds in the DLCA regime. The obtained result agrees with the data obtained by us earlier [28,32]. The initial part of the dependence of R h on time obtained in the absence of HP-␤-CD is linear (line 1 in Fig.…”
Section: Effect Of Hp-ˇ-cd On Thermal Aggregation Of Gapdhsupporting
confidence: 92%
See 3 more Smart Citations
“…This fact indicates that GAPDH aggregation proceeds in the DLCA regime. The obtained result agrees with the data obtained by us earlier [28,32]. The initial part of the dependence of R h on time obtained in the absence of HP-␤-CD is linear (line 1 in Fig.…”
Section: Effect Of Hp-ˇ-cd On Thermal Aggregation Of Gapdhsupporting
confidence: 92%
“…Parameter K LS may be considered as a measure of the rate of aggregation. Earlier we showed that thermal aggregation of GAPDH proceeded in the regime of diffusion-limited cluster-cluster aggregation (DLCA) [26,28,32], and above a definite value of time (t > t*) the dependence of the hydrodynamic radius of the protein aggregates on time followed the power law:…”
Section: Dynamic Light Scattering Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…47,66 It should be noted that a good correlation between the intensity of static light scattering and hydrodynamic size measured with dynamic light scattering is usually observed. 67 Percent inhibition of aggregation (%IA) is typically quantitatively estimated according to 68 : (7) where OD 350(sample) and OD 350(ref ) are the OD values of the protein at a certain wavelength above 320 nm (350 nm in this case) in the presence and absence of a given stress variable over similar incubation times, respectively. In addition to kinetic measurements, thermal aggregation of therapeutic proteins is often probed by this approach in screening for stabilizing excipients and/or formulations.…”
Section: Optical Density As a Measure Of Aggregationmentioning
confidence: 99%